Impact of prophylactic cranial irradiation and hippocampal sparing on 18F-FDG brain metabolism in small cell lung cancer patients. (May 2021) - Chammah, Shaïma El; Allenbach, Gilles; Jumeau, Raphaël; Boughdad, Sarah; Prior, John O.; Nicod Lalonde, Marie; Schaefer, Niklaus; Meyer, Marie
Highlights: Prophylactic cranial irradiation decreases cerebral metabolism diffusely. Hippocampal sparing techniques preserve metabolic activity of the hippocampi. Reducing hippocampal irradiation by 50% is sufficient to preserve their metabolism. Abstract: Background and purpose: Prophylactic cranial irradiation (PCI) in small-cell lung cancer (SCLC) patients improves survival. However, it is also associated with cognitive impairment, although the underlying mechanisms remain poorly understood. Our study aims to evaluate the impact of PCI and potential benefit of hippocampal sparing (HS) on brain metabolism assessed by 18 F-Fluoro-Deoxy-Glucose Positron Emission Tomography/Computed Tomography ( 18 F-FDG PET/CT). Materials and methods: We retrospectively included 22 SCLC patients. 50% had hippocampal-sparing (HS) PCI. 18 F-FDG PET/CT was performed 144.5 ± 73 days before and 383 ± 451 days after PCI. Brain 18 F-FDG PET scans were automatically segmented in 12 regions using Combined-AAL Atlas from MI-Neurology Software (Syngo.Via, Siemens Healthineers). For all atlas regions, we computed SUV Ratio using brainstem as a reference region (SUVR = SUVmean/Brainstem SUVmean) and compared SUVR before and after PCI, using a Wilcoxon test, with a level of significance of p < 0.05. Results: We found significant decreases in 18 F-FDG brain metabolism after PCI in the basal ganglia ( p = 0.004), central regions ( p = 0.001), cingulate cortex ( p < 0.001 ), corpus striata ( p = 0.003), frontal cortex ( p < 0.001 ), parietal cortex ( p = 0.001), the occipital cortex ( p = 0.002), precuneus ( p = 0.001), lateral temporal cortex ( p = 0.001) and cerebellum ( p < 0.001 ). Conversely, there were no significant changes in the mesial temporal cortex (MTC) which includes the hippocampi ( p = 0.089). The subgroup who received standard PCI showed a significant decrease in metabolism of the hippocampi ( p = 0.033). Contrastingly, the subgroup of patients who underwent HS-PCI showed no significant variation in metabolism of the hippocampi ( p = 0.783). Conclusion: PCI induced a diffuse decrease in 18 F-FDG brain metabolism. HS-PCI preserves metabolic activity of the hippocampi.